Enhancing replacement of fishmeal with corn protein concentrate by blending with soy protein concentrate and supplementing attractants in the diets of red hybrid tilapia. (15th July 2022) - Ng, Wing‐Keong; Leow, Tze‐Chin; Yossa, Rodrigue
Abstract: The objective of this study was to investigate the potential of enhancing the dietary substitution of fishmeal (FM) with corn protein concentrate (CPC) in the diets of red hybrid tilapia, Oreochromis sp., by blending CPC with soy protein concentrate (SPC) and adding betaine‐HCl and dried basil leaves (DBL; feeding attractants). Seven isonitrogenous diets [FM100‐CPC0‐SPC0 (control); FM25‐CPC75‐SPC0 (75% of FM replaced by CPC); FM25‐CPC50‐SPC25 (50% and 25% of FM replaced by CPC and SPC, respectively); FM25‐CPC50‐SPC25B (with 0.5% betaine and 2% DBL); FM0‐CPC100‐SPC0 (100% diet protein from CPC); FM0‐CPC75‐SPC25 (75% and 25% of FM replaced by CPC and SPC, respectively) and FM0‐CPC75‐SPC25B (with 0.5% betaine and 2% DBL)] were formulated. Triplicate groups of tilapia fingerlings (average initial weight, 7.31 ± 0.03 g) were fed one of the diets for 56 days. The effects of high dietary levels of plant protein concentrate (PPC) on growth, nutrient utilization, body composition, body colouration and gut histology of tilapia were investigated . High levels of dietary CPC significantly ( p  < 0.05) reduced fish growth and feed intake. Blending CPC with SPC restored the growth performance of tilapia at the 75% PPC inclusion level. The addition of palatability enhancers further improved the growth of tilapia fed high PPC‐based diets.